LABOUR INDUCTION WITH ORAL MISOPROSTOL IN PRE LABOUR RUPTURE OF MEMBRANES AT TERM - Umber Fatima; Mubashra Naz (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: To assess the efficacy of oral misoprostol for induction of labour in women with pre labour rupture of membranes at term and to monitor maternal and fetal complications. Design: Quasi experimental study Settings: Department of Obstetrics and Gynecology, Divisional Head Quarter Hospital, Punjab medical and dental college, Faisalabad. Methods: Selected patients were given 50 µg of oral misoprostol after history, examination and fetal evaluation by reactive CTG.A maximum of 6 doses at 4 hourly interval were given. Oxytocin augmentation was done if required. Main outcome measures: Efficacy that included induction-delivery interval, need for oxytocin infusion, mode of delivery, failed induction, and maternal satisfaction. Fetomaternal complications including nausea and vomiting, pyrexia, uterine hyper stimulation, postpartum hemorrhage, uterine rupture, meconium staining of amniotic fluid, abnormal CTG tracing, low Apgar score at 5 minutes and still birth were secondary outcome measures. RESULTS: Mean induction-delivery interval was 12.8 + 4.24 hours.Nineteen patients 19 (19%) had caesarean section. Failed induction was noted in 2 (2%) cases. Oxytocin augmentation was required in 36(36%) cases. Maternal complications were nausea and vomiting 14(14%), pyrexia 9(9%) and hyper stimulation 3(3%) syndrome. Regarding fetal complications, meconium staining of amniotic fluid was present in 19 (19%) and abnormal CTG pattern in 14 (14%), while no baby had low Apgar score at 5 minutes and there was no still birth. CONCLUSION: Misoprostol is safe and effective method of induction associated with good fetomaternal outcome when used for induction of labour in women with prelabour rupture of membranes at term.